A CROSS-SECTIONAL STUDY ON SCHOOL SOCIAL ENVIRONMENT AND SECONDARY SCHOOL LEARNERS’ ACADEMIC PERFORMANCE IN MBARARA CITY. - Butamanya , George William; Balimutajjo, Suddi; Ahabwe, Emmanuel (Student's Journal of Health Research Africa, 2025)
Background. One of the central objectives of the post-independence education agenda in Uganda was to ensure that all children have access to quality education as a pathway to national development. This study examined the effect of the school social environment on the academic performance of secondary school learners in Mbarara City. Methodology. A descriptive survey research design was employed, targeting a study population of secondary school learners and teachers. The sample size was determined using Krejcie and Morgan’s formula, with respondents selected through stratified and simple random sampling techniques. Inclusion criteria encompassed actively enrolled secondary school learners and teachers, while non-teaching staff and newly transferred students were excluded. Data were collected using questionnaires and an observation checklist. Quantitative data were analyzed using the Statistical Package for Social Sciences (SPSS), generating descriptive and inferential statistics. Results. 271 (73.8%) of the students were male, 98(54.1%) of teachers were within the 25-35 years age bracket, and 66(36.5%) of teachers had between 6-10 years of experience. There was a strong positive correlation between School Social Environment and Learners' Academic Performance, with a Pearson correlation coefficient of 0.644, which was statistically significant at the 0.01 level (p = 0.000), 74.6% of students demonstrated a strong understanding of the subject matter, 66.3% completed assignments on time, and 78.6 % actively participated in class. Further, 73.0% reported a performance improvement, and 70.2% performed well in exams. Conclusion. The study established a statistically significant positive relationship between the school's social environment and academic performance. The study concludes that a conducive school social environment enhances academic performance. Recommendation. Schools should strengthen student-teacher relationships, enhance extracurricular activities, and implement fair discipline policies to foster better learning outcomes.